2019
DOI: 10.7759/cureus.5551
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori: An Underrated Cause of Immune Thrombocytopenic Purpura. A Comprehensive Review

Abstract: Idiopathic thrombocytopenic purpura (ITP) is the autoimmune-mediated destruction of platelets. ITP is a diagnosis of exclusion after other identifiable etiologies have been ruled out. After the first report by Gasbarrini et al. (1998) showing rising platelet counts in ITP patients following Helicobacter pylori (HP) eradication therapy, there is growing evidence that highlights the role of HP in triggering ITP. However, the exact pathophysiology of HP-associated ITP is still unclear, but many theories have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…Another aspect of this association is mediated by the vacuolating cytotoxin A gene (VacA), which is another important virulence factor of H. pylori. VacA perturbs IL-2 signaling, inhibits proliferation of helper T cells, and mediates adherence to platelets [33]. In addition, H. pylori can use the von Willebrand factor (VWF) to increase adherence to platelets [37], resulting in the activation and consumption of platelets, which is another This study has several limitations, including the following: i) The number of studies and patients involved was small; ii) the included studies only examined chronic ITP in adults, and therefore, the results cannot be generalized to patients with acute ITP, especially children; iii) the studies showed heterogeneity in the method used for H. pylori infection; iv) the thresholds for complete response (CR) and partial response (PR) varied among the included studies; and v) some data were missing (such as the duration of ITP).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another aspect of this association is mediated by the vacuolating cytotoxin A gene (VacA), which is another important virulence factor of H. pylori. VacA perturbs IL-2 signaling, inhibits proliferation of helper T cells, and mediates adherence to platelets [33]. In addition, H. pylori can use the von Willebrand factor (VWF) to increase adherence to platelets [37], resulting in the activation and consumption of platelets, which is another This study has several limitations, including the following: i) The number of studies and patients involved was small; ii) the included studies only examined chronic ITP in adults, and therefore, the results cannot be generalized to patients with acute ITP, especially children; iii) the studies showed heterogeneity in the method used for H. pylori infection; iv) the thresholds for complete response (CR) and partial response (PR) varied among the included studies; and v) some data were missing (such as the duration of ITP).…”
Section: Resultsmentioning
confidence: 99%
“…Using different mechanisms, it is believed that H. pylori escapes from innate immune mediators and attaches to gastric epithelial cells. After attachment, one of the important virulence factors of H. pylori , cytotoxin-associated gene A (CagA), induces inflammation through NF-κB signaling and interleukin (IL)-8 stimulation [ 33 , 34 ]. In addition, CagA activates SHP-2 phosphatase and ERK (a mediator of the MPK signaling pathway), which results in the perturbation of gastric epithelial cell signaling [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the pathogenesis of H. pylori-associated ITP is still not confirmed, several studies have mentioned that cytotoxin-associated gene A (cagA), a virulence factor of H. pylori, elicits the production of anti-cagA antibodies that cross react with platelet surface antigens resulting in thrombocytopenia. However, there is a debate about whether the eradication of H. pylori in chronic ITP results in an improvement in platelet count or not [6][7][8]. This study was performed to investigate the impact of treatment of H. pylori infection on platelet count response in chronic ITP children.…”
Section: Introductionmentioning
confidence: 99%